THE RELATIONSHIP BETWEEN MAIN POLYPHENOL COMPONENTS AND FREE RADICAL SCAVENGING ACTIVITY OF SELECTED MEDICINAL PLANTS (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
This study investigates the relationships between the main polyphenols and DPPH radical scavenging activity (RSA) in extracts from some of the most common wild and cultivated species from the Achillea millefolium group, Mentha, Chenopodium botrys, Clinopodium vulgare and Artemisia vulgaris. Another aspect of the study is the effects of choosing an extraction solvent, highlighting the importance of selecting an appropriate one for obtaining extracts with maximum manifested bioactivity. Chemical characterization of compounds is performed. It is based on HPLC-PDA fingerprint profiles, obtained from 70% aqueous methanol extracts. Hydroxycinnamic acids, glycosides of luteolin (LG), apigenin (AG), their aglycones and methoxyflavones are found to be the most abundant components, which have the highest impact on radical scavenging activity (RSA) of the extracts. The data allow supposing high correlation relationships between caffeoylquinic acids and RSA of extracts from four A. millefolium group species and cv. Proa. Cl. vulgare methanol extract, rich in rosmarinic acid, LG and AG, showed the highest RSA with IC50 10.37μg.mL-1. In contrast, extracts of Ch. botrys which lack phenolic acids, contain low amount of glycosides and are rich in methoxyflavone aglycones, possess very weak RSA. For multicomponent analysis, our data suggest 70% methanol as the most appropriate solvent for extraction of compounds belonging to the polyphenol complex. Based on the high quantities of rosmarinic acid, luteolin and apigenin glycosides, 66% ethanol solvent is found to be the best choice for medicinal consumption extracts.